TERAPI WARNA UNTUK MENGURANGI KECEMASAN PADA MAHASISWA - Ainun, Ainun Nur Fitri Ramadhiani; Kholil, Kholil Lur Rochman (JIEGC Journal of Islamic Education Guidance and Counselling, 2024)
Anxiety is a psychological problem most often experienced by students. And generally this anxiety arises because of pressure from social and academic aspects. Of course, this anxiety will have a negative impact on students' potential and academic achievement. Therefore, effective therapy is needed to reduce this anxiety. And one therapy that can be used is non-pharmacological therapy using color therapy with green. The research method used in this research is a literature review approach by analyzing five national journals obtained from the Google Scholar database from 2020-2024. The journal chosen by this researcher was based on inclusive criteria. The criteria set were green color therapy, with the subject of students and anxiety. As for the results of this research, there are three factors that influence green color therapy in reducing student anxiety, namely the characteristics of the color green, color therapy techniques and the duration of therapy.